In Situ Neutron Diffraction Studies on Poling of the Hard PZT Ceramic PIC181. Issue 7 (2nd April 2019) - Eßlinger, Sophia; Neumeister, Peter; Schönecker, Andreas; Hoffman, Mark; Studer, Andrew; Hinterstein, Manuel
Abstract : The poling of hard Lead Zirconate Titanate (PZT) materials is a complex process requiring optimisation of the poling parameters time, temperature, and electric field magnitude. A unique method is presented to monitor the poling process in operando on the unit cell level with neutron diffraction through the analysis of changes in reflection patterns. Diffraction analysis after poling reveals the lattice and domain contributions using poling strain as a measure. This allows for the evaluation of induced dipole alignment and process efficiency. It gives insight into the role of domain wall motions in hard PZT ceramics and how they are affected by poling parameters. Additionally, a poled sample is cycled bipolar and analyzed. It shows a strongly asymmetric strain hysteresis with major contributions from domain wall motions in the tetragonal phase. Macroscopically measured hysteresis loops verify the findings from diffraction. The present work contributes to improving poling results, efficiency and saving energy. The diffraction analysis allows a novel investigation method of the poling mechanisms and provides extensive results that give new insights into the material behavior. With a fundamental research method, this work reveals unprecedented details that can be directly applied to the specific application field of poling technology. Abstract : The material behavior of a hard PZT ceramic, namely the poling mechanisms and domain wall and lattice contributions, are monitored during and after poling using diffraction and a special diffraction analysis method. A powerful means to understand material behavior is provided which allows effective optimization of poling parameters and improvement or adjustment of material performance.